O centenário da ferrovia brasileira (1954): ensaio sobre a elabo-ração da memória ferroviária no Brasil - Oliveira, Eduardo Romero de [UNESP] (My University, 2013)
In 1954, it was celebrated the centenary of railways in Brazil. The date refers to the first section of 14.5 km of railway in Brazil (30/04/1854), in Rio de Janeiro, between Mauá and Fragoso, of the Petropolis Railway Company (Estrada de Ferro Petrópolis). Some of the texts and commemorative events indicated the symbolic values that the railroad took in the Brazilian history. Firstly, on 30.04.1954, the railway section Mauá-Fragoso and steam locomotive “Baroness” (the first used on the track) were declared national monuments(Decree No. 35,447-A, April 30, 1954). Secondly, some entities (Clube de Engenharia, Conselho Nacional de Geografia, Ministério da Viação e Obras Públicas) highlighted the importance of celebrating the Brazilian railway history and its historical significance, economic and geographical. For this, some events was occurred (the commemoration of one hundred years in Rio de Janeiro and Recife on 30.04.1954). Among the texts wrought produced, we highlight the text I Centenary of Brazilian Railroad (1954), released by the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística), and the National Council of Geography (Conselho Nacional de Geografia). The emphasis given to the railway refersto the geographical perspective (territorial expansion), but also makes mention of the Barãode Mauá, the founder of Petropolis Railway Company. We aim to understand the celebration from evocations about the Brazilian railroad history and some ideas that is assigned to the railway (and the Barãode Mauá), and railway heritage (the track and the locomotive “Baroneza”). On basis of this review will seek to understand how it was reconceived the railroad memory in view of these values and material elements.

Em 1954, comemorou-se o centenário das ferrovias no Brasil. A data faz alusão ao primeiro trecho de 14,5 quilômetros de via férrea no Brasil (30/4/1854), no Rio de Janeiro, entre Mauá e Fragoso, da Estrada de Ferro Petrópolis. Alguns dos textos produzidos e eventos comemorativos indicavam os valores simbólicos que a ferrovia tomou na percepção histórica do Brasil. Em primeiro lugar, em 30/4/1954 foram declarados como monumentos nacionais o trecho ferroviário Mauá-Fragoso e a locomotiva a vapor “Baroneza”, que foi utilizada na via férrea (Decreto nº 35.447-A, de 30 de abril de 1954). Em segundo lugar, algumas entidades (Clube de Engenharia, Conselho Nacional de Geografia, Ministério da Viação e Obras Públicas) destacaram a importância de celebrar a história ferroviária brasileira e sua significância histórica, econômica e geográfica. Em função desta data, alguns eventos também ocorreram (festejo das comemorações de cem anos no Rio de Janeiro e em Recife, em 30/4/1954). Dentre o material impresso produzido, ressaltamos o texto I Centenário da Ferrovia Brasileira (1954), lançado pelo Instituto Brasileiro de Geografia e Estatística e Conselho Nacional de Geografia. O destaque atribuído à ferrovia perpassa, por exemplo, a dimensão geográfica (expansão territorial), mas também faz recorrente menção ao Barão de Mauá, o fundador da E. F. Petrópolis. Pretendemos compreender a comemoração a partir das evocações sobre a história da ferrovia, com enfoque num rol de ideias que são atribuídas a ferrovia (e ao Barão de Mauá) e os bens culturais protegidos (o ramal ferroviário e a Baroneza). Em função deste exame, buscaremos entender como se reelaborou a memória ferroviária em vista destes valores e elementos materiais.
Keywords: Memory; Railway heritage; Barão de Mauá; Memória; Patrimonio ferroviário; Barão de Mauá